Integrals and series related to propagators of neural and haemodynamic waves - P. A. Robinson (The Royal Society, 2021)
The propagator, or Green function, of a class of neural activity fields and of haemodynamic waves is evaluated exactly. The results enable a number of related integrals to be evaluated, along with series expansions of key results in terms of Bessel functions of the second kind. Connections to other related equations are also noted.